Plant MicroRNAs Display Differential 3′ Truncation and Tailing Modifications That Are ARGONAUTE1 Dependent and Conserved Across Species([W]) - Zhai, Jixian (American Society of Plant Biologists, 2013)
Plant small RNAs are 3′ methylated by the methyltransferase HUA1 ENHANCER1 (HEN1). In plant hen1 mutants, 3′ modifications of small RNAs, including oligo-uridylation (tailing), are associated with accelerated degradation of microRNAs (miRNAs). By sequencing small RNAs of the wild type and hen1 mutants from Arabidopsis thaliana, rice (Oryza sativa), and maize (Zea mays), we found 3′ truncation prior to tailing is widespread in these mutants. Moreover, the patterns of miRNA truncation and tailing differ substantially among miRNA families but are conserved across species. The same patterns are also observable in wild-type libraries from a broad range of species, only at lower abundances. ARGONAUTE (AGO1), even with defective slicer activity, can bind these truncated and tailed variants of miRNAs. An ago1 mutation in hen1 suppressed such 3′ modifications, indicating that they occur while miRNAs are in association with AGO1, either during or after RNA-induced silencing complex assembly. Our results showed AGO1-bound miRNAs are actively 3′ truncated and tailed, possibly reflecting the activity of cofactors acting in conserved patterns in miRNA degradation.